Pengaruh Sikap Bahasa Penutur terhadap Kematian Bahasa Kerinci dengan Model Sistem Persamaan Diferensial: Kajian Bahasa dan Matematika - Faradhiba Salsabila; Deden Usman Hafidi; Tyla Safitri Widianingrum; Bayu Setiawan; Raihan Dzul Alfaini Pahlevi; Nani Darmayanti (Fakultas Seni Rupa dan Desain ITB, 2022)
Bahasa Kerinci is stable yet endangered, according to Indonesia’s LanguageDevelopment and Fostering Agency. No one can learn a local language because theyounger generation quit using it. This research seeks to determine Bahasa Kerincispeakers’ linguistic attitude, its cause, and its extinction using differential equationmodels. Quantitative and qualitative methodologies are used for this research.Familiarity, social engagement, dialogue outside of intimacy, the relationship betweenBahasa Kerinci and other languages, preservation, and skill are the six domains oflanguage attitude analysis. The research found that teens in Kerinci Regency andSungai Penuh City had a neutral to positive language attitude with an average score of0.599 from all domains. The results also showed that Kerinci Regency teenagers had amore positive language attitude than Sungai Penuh City teens. The informal teaching ofBahasa Kerinci and the atmosphere that supports it influence teens’ linguistic attitudes.Using dynamic mathematical models with three compartments (Bahasa Kerinci’smonolingual speaker, Bahasa Indonesia’s monolingual speaker, and bilingual speaker)and linguistic attitudes, Bahasa Kerinci’s extinction was simulated. Questionnairesdetermine each parameter’s value, including number of speakers, degree of contact, andlinguistic attitudes. Maple software and the Runge-Kutta-Fehlberg method simulatenumerically. The simulation reveals that linguistic attitude maintains and even increasesbilingualism.